A new five-coordinated copper compound for efficient degradation of methyl orange and Congo red in the absence of UV–visible radiation. Issue 46 (4th November 2016) - Han, Li-Juan; Kong, Ya-Jie; Yan, Ting-Jiang; Fan, Lu-Tong; Zhang, Qi; Zhao, Hua-Jun; Zheng, He-Gen
Abstract : A five-coordinated compound, Cu2 (2, 2-bipy)2 (pfbz)4, displays excellent properties of degrading methyl orange and Congo red in the absence of UV–visible radiation. Abstract : A new copper-based coordination compound Cu2 (2, 2′-bipy)2 (pfbz)4 (1 ) (where 2, 2′-bipy = 2, 2′-bipyridine; pfbz = pentafluorobenzoate), was hydrothermally synthesized and structurally characterized. Compound1 having a binuclear structure consists of two copper cations and two oxygen atoms alternately in a plane square arrangement. In the presence of very small amounts of H2 O2, the catalytic properties of compound1 for the degradation of methyl orange (MO) are excellent in the absence of UV–visible radiation. Moreover, compound1 presents suitable properties for degradation of Congo red (CR). Our results indicated that the five-coordinated copper compound, 1, will be a promising candidate for efficient degradation of organic dyes.